Aplikasi Terminal Sidik Jari Dalam Pemantauan Imunisasi Balita - Sugiyanto, Sugiyanto (Universitas Diponegoro, 2011)
Monitoring the implementation of immunization as an effort to achieve a targeted immunization Universal Child Immunization ieimmunization coverage of at least 80% complete on the baby evenly from all over the village / villages in Indonesia. Constraintsrecapitulation of data validation and reporting system is running slow due to the location of posyandu and vulnerable human errorcommitted by the officer. The need for appropriate tools to support the monitoring of immunization activities, by combining hardwareand software in the form of a fingerprint terminal application. This study uses a model of sequential liner system design, software useBorland Delphi 7.0, firebird database, as well as components massanger yahoo as an additional component in Borland Delphi 7.0 forsynchronization of text data transmission between client computers and server computers. Hardware used, fingerprint, personal computers, netbooks and GSM modem. The results of this study, resulting in the application of biometric terminal for monitoringimmunization of infants aged 0 to 11 months, with the performance needs of the time synchronization of data, depending on the speed is relatively fast internet bandwidth used.Keywords : Immunization, Fingerprint